Optimization of production and characterization of a recombinant soluble human Cripto‐1 protein inhibiting self‐renewal of cancer stem cells. Issue 7 (16th May 2022) - Afify, Said M.; Hassan, Ghmkin; Nawara, Hend M.; H Zahra, Maram; Xu, Yanning; Alam, Md Jahangir; Saitoh, Koichi; Mansour, Hager; Abu Quora, Hagar A.; Sheta, Mona; Monzur, Sadia; Du, Juan; et al.
Abstract: Human Cripto‐1 is a member of the epidermal growth factor (EGF)‐Cripto‐FRL‐1‐Cryptic (CFC) family family and performs critical roles in cancer and various pathological and developmental processes. Recently we demonstrated that a soluble form of Cripto‐1 suppresses the self‐renewal and enhances the differentiation of cancer stem cells (CSCs). A functional form of soluble Cripto‐1 was found to be difficult to obtain because of the 12 cysteine residues in the protein which impairs the folding process. Here, we optimized the protocol for a T7 expression system, purification from inclusion bodies under denatured conditions refolding of a His‐tagged Cripto‐1 protein. A concentrations of 0.2−0.4 mM isopropyl β‐D‐1‐thiogalactopyranoside (IPTG) at 37°C was found to be the optimal concentration for Cripto‐1 expression while imidazole at 0.5 M was the optimum concentration to elute the Cripto‐1 protein from a Ni‐column in the smallest volume. Cation exchange column chromatography of the Cripto‐1 protein in the presence of 8 M urea exhibited sufficient elution profile at pH 5, which was more efficient at recovery. The recovery of the protein reached to more than 26.6% after refolding with arginine. The purified Cripto‐1 exhibited high affinity to the anti‐ALK‐4 antibody and suppressed sphere forming ability of CSCs at high dose and induced cell differentiation.